2016
DOI: 10.1122/1.4944993
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity and nonlinear simple shear flow behavior of an entangled asymmetric exact comb polymer solution

Abstract: We report upon the characterization of the steady-state shear stresses and first normal stress differences as a function of shear rate using mechanical rheometry (both with a standard cone and plate and with a cone partitioned plate) and optical rheometry (with a flow-birefringence setup) of an entangled solution of asymmetric exact combs. The combs are polybutadienes (1,4-addition) consisting of an H-skeleton with an additional off-center branch on the backbone. We chose to investigate a solution in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Given the importance of comb polymers as versatile materials in modern society, there is a clear need to understand the molecular origins of complex flow behavior and bulk-scale phenomena. Recent advances in comb polymer synthesis and purification have enabled detailed studies of the bulk rheological properties of well-defined branched polymers. ,,, These studies have shown dramatic effects of molecular-scale architectural defects on bulk rheological properties, such that minor changes in local chain connectivity vastly impact global material response. For example, the onset of nonlinear phenomena occurs at lower flow rates for branched polymers compared to linear polymers of similar molecular weight, , with strain hardening becoming strikingly more pronounced as the branch molecular weight is increased in comb polymer melts.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of comb polymers as versatile materials in modern society, there is a clear need to understand the molecular origins of complex flow behavior and bulk-scale phenomena. Recent advances in comb polymer synthesis and purification have enabled detailed studies of the bulk rheological properties of well-defined branched polymers. ,,, These studies have shown dramatic effects of molecular-scale architectural defects on bulk rheological properties, such that minor changes in local chain connectivity vastly impact global material response. For example, the onset of nonlinear phenomena occurs at lower flow rates for branched polymers compared to linear polymers of similar molecular weight, , with strain hardening becoming strikingly more pronounced as the branch molecular weight is increased in comb polymer melts.…”
Section: Introductionmentioning
confidence: 99%
“…During most processing operations, deformations are large and rapid, and thus, nonlinear material responses are required to evaluate real systems. Various nonlinear deformations, such as nonlinear step shear, , transient start-up shear, and extensional flow, have been used because nonlinear deformations induce molecular chain changes, which are reflected by nonlinear viscoelastic properties. However, subtle differences in architecture may not be detected by even nonlinear measurements mentioned above.…”
Section: Introductionmentioning
confidence: 99%